The electrochemical behavior’s character of a potential antiviral drug 3-nitro-4-hydroxy-7-methylthio-4H-[1,2,4]triazolo[5,1-c][1,2,4]triazinide monohydrate - Polina N. Mozharovskaia; Alexandra V. Ivoilova; Roman A. Drokin; Alla V. Ivanova; Alisa N. Kozitsina; Vladimir L. Rusinov (Chimica Techno Acta)
The results of this study of the electrochemical transformation of 3-R-4-hydroxy-1,4-dihydro-7-X-1,2,4-triazolo[5,1-c][1,2,4] obtained by voltammetry are presented. It was found that 3-R-4-hydroxy-1,4-dihydro-7-X-1,2,4-triazolo[5,1-c][1,2,4] derivatives are capable of electrochemical reduction in the potential range of –0.28 to –0.33 V (relative to Ag/AgCl) in Britton–Robinson buffer at pH = 2. The electrochemical behavior of the sodium salt of 3-nitro-4-hydroxy-7-methylthio-4H-[1,2,4]triazolo[5,1-c][1,2,4]triazinide monohydrate (compound 1), which in silico modeling predicted possible biological activity against various tick-borne encephalitis and Coxsackie B3 viruses. At the potentials of the first stage of electroreduction at pH = 2, the main transformation process is the three-electron reduction scheme of the nitro group of compound 1. It was established that compound 1 in an aprotic medium is reduced in ionic form, most likely in the form of an ion pair with the Na+ cation, and in an aqueous medium in the form of a protonated particle. Based on this, a scheme was proposed for the probable electrochemical transformation of the studied compound.